Comprehensive Assessment of the STIMs and Orais Expression in Polycystic Ovary Syndrome - Song, Tian; Li, Ping; Wang, Qiumin; Hao, Baozhen; Wang, Ying; Bian, Yuehong; Shi, Yuhua (Frontiers in Endocrinology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disease characterized by irregular menstrual, hyperandrogenism and polycystic ovaries. The definitive mechanism of the disorder is not fully elucidated. Store-operated Ca2+ entry (SOCE) plays a role in glucose and lipid metabolism, inflammation, hormone secretion and cell proliferation. STIMs and Orais are the main elements of SOCE. The potential role of SOCE in PCOS pathogenesis remain unclear. Methods: The expression of STIMs and Orais in granulosa cells (GCs) derived from 83 PCOS patients and 83 controls were analyzed respectively by using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Binary regression analysis was used to identify the factors affecting PCOS after adjusted by BMI and age. Pearson correlation analysis was used to determine the association between PCOS phenotypes and SOCE genes expression. Results: Significantly increased expression of STIM1, STIM2, Orai1 and Orai2 were observed in PCOS patients compared with controls (P=0.037, P=0.004， P≤0.001 and P=0.013 respectively), while the expression of Orai3 was decreased (P=0.005). And the expression levels of STIMs and Orais are identified as the factors affecting PCOS (P<0.05). The expression of these genes correlated with hormone level and antral follicle count (P<0.05). Conclusions: For the first time our findings indicated that the elements of SOCE were differently expressed, with STIM1, STIM2, Orai1and Orai2 significantly increased while Orai3 decreased in PCOS GCs, which might be dominantly involved in dysfunction of ovarian granulosa cells and hormonal changes in PCOS.